Drawing Down Retirement Financial Savings: A Welfare Analysis using French data - Freitas, Najat El Mekkaoui de (2021)
Bravo, J. M., & Freitas, N. E. M. D. (2021). Drawing Down Retirement Financial Savings: A Welfare Analysis using French data. In 2021 The 5th International Conference on E-Commerce, E-Business and E-Government (ICEEG '21) (pp. 152-158). Association for Computing Machinery (ACM). https://doi.org/10.1145/3466029.3466041 -------------------------------------------------------------- Funding Information: Najat El Mekkaoui acknowledges support by Groupama Gan Vie, Groupama Asset Management and Deloitte. Jorge M. Bravo acknowledges financial support by Portuguese national funds through FCT under the project UIDB/04152/2020 - Centro de Investigação em Gestão de Informação (MagIC). Publisher Copyright: © 2021 ACM.